1982
DOI: 10.1007/bf00387900
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of anthocyanoplasts in red-cabbage

Abstract: A study of the ultrastructure of anthocyanoplasts from the seedling hypocotyl and leaves from the heart of red-cabbage plants has been made. Evidence is presented that the anthocyanoplast does not represent a hydrophobic droplet but is bounded by a single tripartite membrane approximately 10 nm in thickness. The results provide further support for the view that the anthocyanoplast is an intracellular compartment containing at least the later enzymes of anthocyanin biosynthesis, which are thereby separated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 6 publications
0
27
1
Order By: Relevance
“…Many of these structures could correspond to early intermediates in AVI formation when anthocyanins are enclosed into tonoplast cup-shaped domains. In addition, AVIs have been reported to have or lack a membrane (Small and Pecket, 1982;Nozue et al, 1993;Markham et al, 2000;Zhang et al, 2006;Conn et al, 2010). We have observed that the tonoplast-derived membrane that surrounds free AVIs in the vacuolar lumen can partially degrade; therefore, depending on the stage, AVIs can partially lose their membranes.…”
Section: Avis Arise From Microautophagy Of Cytoplasmic Anthocyanin Agmentioning
confidence: 64%
See 1 more Smart Citation
“…Many of these structures could correspond to early intermediates in AVI formation when anthocyanins are enclosed into tonoplast cup-shaped domains. In addition, AVIs have been reported to have or lack a membrane (Small and Pecket, 1982;Nozue et al, 1993;Markham et al, 2000;Zhang et al, 2006;Conn et al, 2010). We have observed that the tonoplast-derived membrane that surrounds free AVIs in the vacuolar lumen can partially degrade; therefore, depending on the stage, AVIs can partially lose their membranes.…”
Section: Avis Arise From Microautophagy Of Cytoplasmic Anthocyanin Agmentioning
confidence: 64%
“…AVIs were described as being surrounded by a single membrane in grapevine and in red cabbage (Brassica oleracea). In sweet potato (Ipomea batatas), carnation (Dianthus caryophyllus), and lisianthus (Eustoma grandiorum), AVIs appear to lack surrounding membranes and instead consist of a protein matrix or thread-like structures (Small and Pecket, 1982;Nozue et al, 1993;Markham et al, 2000;Zhang et al, 2006;Conn et al, 2010). Besides anthocyanins, AVIs have been reported to contain a metalloprotease called VP24 in sweet potato (Nozue et al, 1997(Nozue et al, , 2003Xu et al, 2001) and tonoplast membrane lipids in grapevine cultured cells (Conn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Herein it is used to refer to ER-derived biosynthetic vesicles, while AVIs, which shall be used hereafter, refer to vacuolar-associated bodies as per Poustka et al (2007) and Pourcel et al (2010). identified (Conn et al 2003). Another difference noted among species are contradictory microscopy reports showing the presence (Pecket and Small 1980;Small and Pecket 1982;Yasuda and Kumagai 1984;Jasik and Vancova 1992;Poustka et al 2007) and absence (DeusNeumann 1983;Nozue et al 1993;Kubo et al 1995;Markham et al 2000) of membranes surrounding the AVIs. Finally, the non-vacuolar localisation of anthocyanoplasts in some reports in grape (Calderon et al 1993), radish (Nozzolillo and Ishikura 1988) and rose (Yasuda 1974(Yasuda , 1979 provide evidence that AVIs are not homologous between plant species and that they may move between cellular compartments.…”
Section: Introductionmentioning
confidence: 85%
“…Anthocyanins have been repeatedly found in inclusions in several plant species with no clear phylogenetic relation including lisianthus, sweet potato, red cabbage or grapevine (Pecket and Small, 1980 ;Small and Pecket, 1982 ;Nozue and Yasuda, 1985 ;Conn et al, 2003 ;Irani and Grotewold, 2005 ;Zhang et al, 2006) . Interestingly, anthocyanin-filled inclusion occur in the cytoplasm as well as in the vacuole itself where the vacuolar bodies are generally referred to as ' a nthocyanic v acuolar i nclusions' (AVIs) (Markham et al, 2000) .…”
Section: On the Road Again: Transport Versus Trafficking And The Dawnmentioning
confidence: 94%